La négociation des sentences du point de vue des avocats de la défense - Poirier, Robert (Criminologie, 1987)
This article discusses the findings of empirical research into the working habits of defence attorneys. Contrary to what is implied by the current expression “plea bargaining”, it is not the plea but the sentence which is the real object of the negotiations taking place between the prosecution and the defence. When no agreement is reached between the Crown prosecutor and the defence attorney, they resort to formal representations made before the judge during a sentencing hearing and argue for their conflicting recommendations. Hence, it is not a criminal trial but a formal sentencing hearing, where both parties argue their case, which is the outcome of a failure of the Crown and defence attorney to reach a negotiated agreement on the fate of a defendant.